Perbedaan Jumlah Keberadaan Bakteri Escherichia Coli Pada Es Batu Yang Berbahan Baku Air Pdam Dan Non Pdam Pada Penjual Minuman Disekitar Stadion Manahan Surakarta - Fajriaty, Nabila Rasyida (2016)
Background: Water is the main ingredient of ice cube thus it has to fulfill the standard. Water sources that is mostly used by community are PDAM water, pond water, well water and raining water. The indicator of water hygiene is the absence of Escherichia coli Aim: To know the water quality and the number of Escherichia coli presence in ice cubes sold around Manahan Sport Center Surakarta Method: This study usedprimary data from direct observation in 39 stalls around Manahan Sport Center Surakarta Result: There were 14,55% from 19 samples of ice cubes made from PDAM water contaminated by E. coli bacteria but still fulfilled the standard for consumption. Meanwhile, there were 25% from ice cubes made from non PDAM water and there were 267 E. coli bacteria was found per 100 ml thus it didn't meet the standard for consumption Conclusion: There is a difference of E. coli contamination between ice cubes made from PDAM water and non PDAM water and non PDAM water that is sold in drinking stalls around Manahan Sport Center Keywords: ice cubes, water, PDAM, E. coli 1 Students of Faculty of Medicine Muhammadiyah Surakarta University 2 Lecturer of Faculty of Medicine of Muhammadiyah Surakarta University